Existence of Periodic Solutions for Shunting Inhibitory Cellular Neural Networks with Neutral Delays - Ninghua Chen (Discrete Dynamics in Nature and Society)
This paper considers the existence of periodic solutions for shunting inhibitory cellular neural networks (SICNNs) with neutral delays. By applying the theory of abstract continuation theorem of k-set contractive operator and some analysis technique, a new result on the existence of periodic solutions is obtained.